Nilai Taubat dalam Lirik Lagu Forgive Me Karya Maher Zain: Analisis Semiotika Roland Barthes - Dadan Firdaus; Dzulkhaffi Muhammad Arieful Husna; Laila Qadera Fitria; Muhammad Fuad Ramadhan; Syahla Fatia Zahra (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study examines the representation of repentance (tawbah) in the lyrics of Maher Zain's song “Forgive Me” using Roland Barthes' theory of semiotics, viewed through the lens of Islamic moral teachings within the Sufi tradition. Released in 2009 on the album Thank You Allah, the song conveys a profound spiritual narrative of sin-awareness, remorse, and a sincere yearning for divine forgiveness. Employing a qualitative-descriptive approach, the lyrical text is examined at three levels of meaning based on Barthes' framework: denotation, connotation, and myth. The findings are then interpreted through the tawbah frameworks of Al-Ghazali (ilm, hal, and amal), Al-Qushayri (the spiritual stations of repentance), and Ibn Qayyim al-Jawziyyah (mahabbah and khawf). The results show that the lyrics of “Forgive Me” encompass all three core dimensions of tawbah: at the cognitive level, an awareness of wrongdoing; at the connotative level, genuine remorse coupled with a sincere desire to change; and at the mythological level, a belief in divine forgiveness and the necessity of seeking it. This study contributes to the field of contemporary Islamic literary studies by demonstrating that popular religious music can serve as a meaningful medium for expressing and transmitting Sufi spiritual values to a global audience.